Educação infantil, ciência e tecnologia: um estudo de caso sobre a formação docente em tempos de pós-modernidade - Mondini, Marta Silva Lima (2024)
This thesis is an investigation into teacher training for the development of scientific education in early childhood education with the arrival of the Mobile Lighthouses of Knowledge in the Municipal Early Childhood Education Centers of the Municipal Department of Education of Curitiba in 2022. Thus, the research question was the following: what are the contributions of teacher training from the perspective of Freirean pedagogy to the development of scientific education in early childhood education in postmodern times? The general objective of the work was to reflect on the training of teachers based on Freirean pedagogy that collaborated with the emancipation of teaching work through the critical understanding of the postmodern narrative. The specific objectives were: to develop a methodological path for teacher training from the perspective of unveiling the postmodern narrative; to analyze how the technological artifacts present at Farol do Saber could support and enrich the projects, establish coding and decoding dialogues and generating themes, in order to identify subsidies for a dialogical-problematizing teaching practice and discuss the results of this methodological training path observing the child’s protagonism and the emancipation of the teaching work. The methodology chosen to answer the research question was the qualitative one in the case study approach. Discourse analysis was chosen to understand the discursive material collected during the research. The research results showed that if teachers are involved in critical, dialogic and collectively constructed teacher training, it is possible to develop work with science and technology in early childhood education, valuing the children’s prior knowledge, their curiosities and questions, building knowledge with them about the reality that surrounds them in the constitution of a critical scientific education. This emancipatory and authorial teaching practice strengthens the school and the CMEIs in their educational task, breaking with paradigms of postmodern discourse that devalues science and education.